UJI AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN DOLLAR (Ficus pumila L.) - Muh. Naufal Hisyam; Daniel Daniel; Eva Marliana; Agustina R. M. (PROSIDING SEMINAR KIMIA, 2022)
Ornamental plants are one of the resources that have the potential to be developed on a large scale due to high public interest. The dollar leaf plant is one of the most common ornamental plants. The leaves of the dollar plant are commonly used in traditional medicine. The objective of this research was to determine the antioxidant properties by means of the 2,2 diphenyl -1-picryhidrazil (DPPH) method from the methanolic extract of dollar leaf (Ficus pumila L.). Based on the results of phytochemical tests, the methanol extract is known to contain alkaloids and steroids. The dollar leaf methanolic extract showed antioxidant activity with an IC50 value of 387.753 mg/mL. From the antioxidant activity test results, dollar leaf methanol extract has relatively weak antioxidant power. Keywords: dollar leaf, antioxidant, 2,2 diphenyl -1-picryhydrazyl (DPPH) method, extract